2017
DOI: 10.1507/endocrj.ej16-0494
|View full text |Cite
|
Sign up to set email alerts
|

High insulin impaired ovarian function in early pregnant mice and the role of autophagy in this process

Abstract: METABOLIC DISORDERS, such as PCOS (polycystic ovary syndrome) and T2DM (type 2 diabetes mellitus), are reported to be associated with high miscarriage rates, decreased pregnancy rates, and low live birth rates [1]. PCOS and T2DM are characterized by hyperinsulinemia [2]. PCOS is an endocrine and metabolic disorder with a prevalence ranging from 5 to 13% in women of reproductive age. Moreover, PCOS is often accompanied by menstrual dysfunction, anovulaHigh insulin impaired ovarian function in early pregnant mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
1
13
2
Order By: Relevance
“…Meanwhile, elevated insulin levels and/or insulin resistance are commonly seen in women with PCOS, and this is one of the most important mechanisms in PCOS pathogenesis [31,32]. It was found to be able to impair ovarian autophagy and function in mice [33]. Recently, insulin-sensitizers such as inositol have been used to improve the insulin resistance in PCOS by regulating autophagy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, elevated insulin levels and/or insulin resistance are commonly seen in women with PCOS, and this is one of the most important mechanisms in PCOS pathogenesis [31,32]. It was found to be able to impair ovarian autophagy and function in mice [33]. Recently, insulin-sensitizers such as inositol have been used to improve the insulin resistance in PCOS by regulating autophagy [34].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5C, an undetectable level of autophagy-related protein LC3B (microtubule-associated protein 1 light chain 3) (Jiang et al, 2017) was observed in the oocytes of TGFA SFs, whereas the oocytes of WT and TGF normal follicles displayed a normal level of LC3B. This result demonstrates that autophagy activity of the oocytes of TGFA follicles, which is fundamental to the cellular processes of the oocytes, was largely weakened (Su et al, 2017).…”
Section: Resultsmentioning
confidence: 82%
“…5C, an undetectable level of autophagy-related protein LC3B (microtubule-associated protein 1 light chain 3)(Jiang et al, 2017) was shown in oocytes of TGFA SFs, while oocytes of WT and TGF normal follicles displayed a normal level of LC3B. This result demonstrated that autophagy activity of the oocytes of TGFA follicles was largely weakened, which was fundamental to many oocyte cellular processes(Su et al, 2017).…”
Section: Resultsmentioning
confidence: 98%